(untitled) (E Global Congress, 2025)
Urinary stone disease (UST) is one of the most common diseases in the world. According to several studies, the global prevalence of UST is 3.5-9.6%. Urolithiasis is the third most common urological disease and accounts for 30-40%. When examining studies on a country-by-country basis, the prevalence of UST is 5-10% in European countries, 7-15% in the USA, 20% in Arab countries, and 1-5% in Asian countries. In calcium oxalate urolithiasis, the presence of crystalluria in the urine indicates the presence of general and specific metabolic disorders, which are characteristic of the disease.